Energy Productivity and Efficiency of Lowland Rice (Var. PSB Rc18) Under Various Organic Nutrient Sources and Quantum Enhancers - Ratilla, Berta C.; Mendoza, Teodoro C. (Annals of Tropical Research, 2016)
Energy analysis is not usually given much emphasis in crop production despite the latter’s huge dependence on oil and fuel. This study was conducted for two cropping seasons to assess whether the use of various nutrient sources can increase yield, energy productivity, and use efficiency of lowland rice (PSB Rc18). All production inputs and activities were accounted and energy analysis was done using energy coefficients adopted by previous researchers. Parameters on grain yield, energy expenditures, energy productivity, efficiency, and intensity were taken. Rice applied with organic fertilizer from unenhanced composted cow manure (UECM) yielded significantly higher by 61% and 18% than the untreated control and the full inorganic treatment, respectively. Quantum and organic nutrient sources spent 69.18-71.79 liter diesel oil equivalent (LDOE) ha-1 which is 2-3 times lesser than the use of sole inorganic or combined with organic nutrient sources (142.13-225.74 LDOE ha-1), thus giving significantly higher energy productivity and efficiency. Unenhanced composted cow manure was the most productive and efficient in terms of energy use by 1.59 and 3.73 times over the control and full inorganic treatment, respectively. Energy spent to produce a ton of unmilled rice was markedly reduced by 53% from organic fertilization due to lower energy intensities (15.95-25.16 LDOE t-1 grain) than inorganic treatments (36.50-60.89 LDOE t-1 grain). Hence, at this time of energy crisis and climate change, organic farming which includes use of quantum enhancers is a potential option in improving energy resource effectiveness of PSBRc18.